Perspective of Parental Satisfaction with Academia of Children with Down Syndrome and Intellectual Disability - Maham Ashraf, Muhammad Azzam Khan, Bareera Saeed, Saba Aziz, Fahad Masood, Muhammad Ahmed, Arslan Saleem Chugtai (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Down syndrome is the disorder in which physical, mental, and functional deformity is present due to trisomy twenty one, the existence of three chromosomes instead of two normal chromosomes in human genome. Children who have intellectual disability they have neurodevelopmental deficit regards to limited in intellectual operation and adaptive behaviors. One of the safeguards variables as a favorable adaptability to a challenging conditions, like managing a handicapped kid, is marital satisfaction. Higher levels of marital happiness are linked to reduce depression levels, less parenting stress, and better parental planning (Kersh, Hedvat, Hauser-Cram, & Warfield, 2006) Objective(s): To find out parental satisfaction with academia of Down syndrome and Intellectual disability in Pakistan. Methodology: A standardized tool PSCDDI is used and data were collected from special education school of Lahore and Gujranwala city. Data were collected from 385 parents of down syndrome and intellectual disable child parents through questionnaire which were provided to parents and take their opinion. After data collected we analyze the data and concluded the results. Results: In this study we find out that parents are unsatisfied to academic performance of their child most of child and most of the parents are not sure and disagree. Down syndrome child are 38.9% and 60.9% child were intellectual disable and they are all in pre to 3rd grade. Most of the child were in the age range of 5- 8 years. The parents of DS and ID child have non-Consaginous marriage is 53.6% and 46.4% are Consaginous marriage. Conclusion(s): The overall study of parental satisfaction towards the developmental disability of their children shows unsatisfaction. . In Pakistan parents who have their children with disability faced many challenges in society. Keyword: Down syndrome, intellectual disability, parental satisfaction, academia